Noise-induced hearing loss in a paper mill in KZN, South Africa - Viljoen, Christina Adriana (My University, 2008)
ABSTRACT It is well documented that repetitive exposures to high intensity sound can cause acoustic trauma to the ear resulting in hearing loss, and that occupational noise is a significant cause of adult-onset hearing loss. Research world wide has indicated a significant number of workers with hearing loss attributed to noise exposure. Noise-Induced Hearing Loss (NIHL) claims are responsible for the majority of occupational disease payouts. The study was undertaken in order to determine the extent of hearing loss due to noise exposure that could be ascribed to excessive exposure to noise, and to describe the noise-induced hearing loss by severity, type of work, and area of work and duration of service. The cross-sectional study included 466 workers employed in a pulp and paper mill in KwaZulu Natal (KZN) South Africa. It involved the assessment of 932 individual audiograms to diagnose noise-induced hearing loss and the calculation of the percentage loss of hearing from pre placement to the year 2005. Audiometry results were presented for noise-induced hearing loss in relation to area of work, duration of service, categories of severity and age group. The prevalence of noise-induced hearing loss in the pulp and paper mill was 21% (98/466) and with 79% (368/466) of workers whose audiograms returned results not indicating NIHL. 75 workers were excluded due to workplace transfers. Type of work, area of work and years of service correlated significantly with a diagnosis of noise-induced hearing loss. As a department, the wood yard (which included the wood chipping facility, maintenance workers and workers with 10 – 20 years of service) showed the most significant association. In categories of severity 16.7% of workers suffering from NIHL fall in the ≤ 5 Percentage Loss of Hearing PLH category. This study has confirmed the findings of others that noise exposure is a significant hazard in industry and an effective noise control programme is the only way to reduce the risk of NIHL. _____________________________________________________________________
Keywords: noise induced hearing loss; paper mill